Propostas educacionais nos discursos de intelectuais da geração 1870: ideias para um Brasil moderno (1870-1889) - Santos, Laisa Dias (2021)
This research aims to understand the meanings attributed to the idea of modern instruction in educational writings of 11 Brazilian intellectuals of the 1870 generation. For that, it was necessary to: identify in the intellectual itineraries the genealogy of origin of educational writings, paying attention to themes, typology of works, means of transmission used and the places of speech of their authors; to analyze the interlocutions established between educational discourses, foreign theories and the conjuncture of national education at the end of the Brazilian Empire; and to interpret how the idea of modern instruction was configured, paying attention to the similarities and divergences between the educational writings analyzed. To achieve the objectives, the approach of the History of intellectuals was used, according to Sirinelli (1996), combined with documentary research and the technique of prosopography. As research sources, laws, decrees, parliamentary speeches, newspaper articles, conferences, reports and public education reform projects prepared by Aarão Reis, Alberto Sales, Antônio da Silva Jardim, Rangel Pestana, Joaquim Nabuco, Luís Pereira Barreto were analyzed , Miguel Lemos, Raimundo Teixeira Mendes, Rui Barbosa, Silvio Romero and Tobias Barreto. The surveys of sources were carried out in physical and digital archives of institutions such as Fundação Getúlio Vargas (FGV); Center for Research and Documentation of Contemporary History of Brazil (CPDOC); Brasiliana Guita and José Mindlin Library; Library of the Faculty of Law of Pernambuco and São Paulo; Pedro Aleixo Library; Digital Library of the Federal Senate; National Library; Brazilian Academy of Letters and Historical and Geographic Institute of Brazil. It was possible to perceive that the 11 intellectuals analyzed, in their educational productions with a view to modern instruction, prioritized the defense of the principles of freedom, scientificity and secularism of teaching, the result of a scientific mentality, engendered both by places of inspiration, engagement and placement. ideas, such as the press, educational establishments and political spaces, as well as foreign theories and a historical vision of the country's transition, transformation and modernization. Finally, to think about education and its problems in the writings of the 1870 generation, is to think beyond the field of teaching and its particularities, correlating them to changes in society, economics, politics, religion, culture and to new moral values resulting from a society that was intended to be modern.